Sibelius Ultimate Application in Learning Tamtatitu Rhythm Patterns in Phase E Use of Sibelius Ultimate Application in Learning Rhythm Patterns in Phase E - Rini Arifa Hidayamastifa; Iswandi (International Journal of Global Sustainable Research, 2023)
This study aims to determine how the learning process of tamtatitu rhythm patterns using the sibelius ultimate application in grade X or phase E students at SMAN 1 Rambat Tanah Datar Regency. This type of research is qualitative using a naturalistic approach. Based on the results of the study, teachers explored the implementation of forms and notation values as well as tone pyramids using animated videos. In the TAM TA TI TU rhythm pattern, there are four kinds of syllables that are interpreted with sixteenth note notation. The rhythm pattern is played right in the tap of a long needle. Silence on each syllable is marked 0. After implementing the rhythm pattern, students are invited to work to play the rhythm pattern and write it on the sibelius ultimate application. The relationship between learning rhythm patterns and the applications used makes students understand better in terms of the practice process. Students feel more able to explore with the application rather than using the latest media and innovations.